Implementation of Agenda Setting Theory by Radio Republic of Indonesia Denpasar As A Media for Political Literacy - Muskita, Marleen; Putri, Rima Dewanti (Universitas Pendidikan Nasional, 2023)
The development of information technology is now increasingly making it easier for people to receive information, because all the current news with technological advances, the media now provides easy access for its audience. Advances in information technology have had an impact on the mass media in presenting information, one of the mass media which has also experienced developments in presenting information to the public, namely radio. The purpose of this research is to find out the implementation of agenda theory by Radio Republik Indonesia Denpasar as a medium for political literacy. In this study using a qualitative descriptive research approach to the type of descriptive descriptive research. The data analysis techniques used in this study were data collection, data reduction, data presentation, and drawing conclusions. The result of this research is that in implementing the agenda setting theory, Radio Republik Indonesia Denpasar has fulfilled its role as a political literacy media that provides education and knowledge to its listeners. However, this has not run optimally, due to the limitations of Radio Republik Indonesia Denpasar in reporting on political issues, so it is a challenge for Radio Republik Indonesia Denpasar to be able to package political information that is controversial in nature so as not to lead public opinion and genuinely educate listeners.